Resistencia antibiótica frente a Neisseria gonorrhoeae en centros de atención médica periódica de la ciudad de Iquitos-Perú en los años 2017-2020 - Siguas Peixoto, Bertha Karina (2022)
In Peru, a surveillance system against Neisseria Gonorrhoeae is not implemented. We do not have information on the prevalence of resistance in patients with Neisseria gonorrhoeae infection in our Loreto region. The objective of this research was to determine antibiotic resistance against Neisseria gonorrhoeae in two periodic medical care centers in the city of Iquitos-Peru in the years 2017-2020. The observational research design, cross-sectional, retrospective descriptive design. A total of 51 samples were analyzed, finding a total of 22 positive cases for N. gonorrhoeae, of which 95.5% were isolated from male patients. The men had a mean age of 23 years, and the only female patient was 17 years old. The majority worked independently (36.4%), and 31.8% were students. 63.6% had basic school education studies and more than half (54.5%) belonged to the district of San Juan. The majority attended due to symptoms, with urethral discharge being the most common clinical picture. About half had a history of STIs, the majority being candida and gonorrhea; 9.1% of the participants had a history of HIV and most of them 95.5% would not have received specific treatment for gonorrhea infection. In the behavioral characteristics, 72.7% were heterosexual and 27.3% had risky sexual behavior of male sex men (MSM); and only 22.7% of patients reported having multiple sexual partners. Penicillin, Ciprofloxacin and Doxycycline presented antimicrobial resistance against Neisseria gonorrhoeae, with 59.1%; 45.5%; and 31.8% respectively. On the other hand, Ceftriaxone, Azithromycin had a sensitivity profile of 100%. It is concluded that Penicillin, Ciprofloxacin and Doxycycline show a pattern of high resistance against Neisseria gonorrhoeae and instead Ceftriaxone and Azithromycin are sensitive in their entirety.